The zone of interest - Amis, Martin (Vintage Books, 2015)
"From one of England's most renowned authors, an unforgettable new novel that provides a searing portrait of life - and, shockingly, love - in a concentration camp. Once upon a time there was a king, and the king commissioned his favorite wizard to create a magic mirror. This mirror didn't show you your reflection. It showed you your soul -i t showed you who you really were. The wizard couldn't look at it without turning away. The king couldn't look at it. The courtiers couldn't look at it. A chestful of treasure was offered to anyone who could look at it for sixty seconds without turning away. And no one could. The Zone of Interest is a love story with a violently unromantic setting. Can love survive the mirror? Can we even meet each other's eye, after we have seen who we really are? In a novel powered by both wit and pathos, Martin Amis excavates the depths and contradictions of the human soul"